The Beauty of the Seoul: Determinants of Korean Cosmetic Usage among Young Filipina University Students - Correa, Olivia Maria D.; Villamonte, Gabriella M.; Manaois, Alexa D.; Basto, Orange Q.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The global ascendancy of Korean cosmetic products, propelled by the Korean Wave phenomenon, has fundamentally reshaped beauty standards and consumer behaviors worldwide. This study aimed to determine the factors influencing the use of Korean cosmetics among female university students in the Philippines, focusing on perceived authenticity, aesthetic appeal, and facial perception. A structured questionnaire was administered to 175 respondents from a private university in Metro Manila. Data were analyzed using descriptive and inferential statistics, including Spearman's rank correlation coefficient and regression analysis. Results indicated a statistically significant positive correlation between the perceived aesthetic appeal of packaging (β = .211, p < .006) and the usage of Korean cosmetics. Regression analysis confirmed that perceived aesthetic appeal was a determinant of product usage (R2 = 0.176, P ≤ 0.05). Facial attractiveness (β = .107, p = .165) were found to be statistically significantly correlated with usage, however, found to be not statistically significant determinant. Perceived authenticity (β = .005, p = .950) showed no correlation with product usage and not a determinant as well. These findings underscore the importance of visual aesthetics in consumer behavior among young Filipino consumers, providing strategic insights for brands in the competitive beauty market of the Philippines.